Interioridade E Paisagem Urbana Na Poesia Dos Anos 1920 De Ribeiro Couto - Batista, Thiago Rodrigues [UNIFESP] (2018)
This Work Aims To Analyze The Initial Work Of Brazilian Poet Rui Ribeiro Couto, Composed By His Three First Books, Published In The 1920s, With Emphasis On The Third One, Um Homem Na Multidão, 1926. The Research Main Purpose Is The Close Reading Of Style Elements That Contribute To The Construction Of What We Understand As An Interiority That, In Many Of His Poems, Fuses Itself With The Landscape Observed By The Lyric Self. The Emphasis On 1926's Work Is Due To The Fact That There Is A Major Presence Of The City As A Poetical Theme, Central Subject Of Research. Being An Author Whose Critical Fortune Is Still Sparse, We Organized, In A General Way, Part Of The Critical Texts That Deal With The Initial Moment Of His Work. With This, We Try To Understand, Some Of The Causes Of Some Oscillation Of The Critical Interest By Its Books. Complementarily To The Task Of Organizing His Critical Fortune And With The Intention Of Giving To His Initial Work A Reading In A Alternative Critical Base That Are Presupposed In Th